Brain and lower body protection during aortic arch surgery. Issue 12 (20th November 2022) - Calafiore, Antonio M.; de Paulis, Ruggero; Iesu, Severino; Paparella, Domenico; Angelini, Gianni; Scognamiglio, Mattia; Centofanti, Paolo; Nicolardi, Salvatore; Chivasso, Pierpaolo; Canosa, Carlo; Zaccaria, Salvatore; de Martino, Luigi; et al.
Abstract: Background: Deep hypothermic circulatory arrest (DHCA) at ≤20°C for aortic arch surgery has been widely used for decades, with or without cerebral perfusion (CP), antegrade (antegrade cerebral perfusion [ACP]), or retrograde. In recent years nadir temperature progressively increased to 26°C–28°C (moderately hypothermic circulatory arrest [MHCA]), adding ACP. Aim of this multicentric study is to evaluate early results of aortic arch surgery and if DHCA with 10 min of cold reperfusion at the same nadir temperature of the CA before rewarming (delayed rewarming [DR]) can provide a neuroprotection and a lower body protection similar to that provided by MHCA + ACP. Methods: A total of 210 patients were included in the study. DHCA + DR was used in 59 patients and MHCA + ACP in 151. Primary endpoints were death, neurologic event (NE), temporary (TNE), or permanent (permanent neurologic deficit [PND]), and need of renal replacement therapy (RRT). Results: Operative mortality occurred in 14 patients (6.7%), NEs in 17 (8.1%), and PNDs in 10 (4.8%). A total of 23 patients (10.9%) needed RRT. Death + PND occurred in 21 patients (10%) and composite endpoint in 35 (19.2%). Intergroup weighed logistic regression analysis showed similar prevalence of deaths, NDs, and death + PND, but need of RRT (odds ratio [OR]: 7.39, confidence interval [CI]: 1.37–79.1) and composite endpoint (OR: 8.97, CI: 1.95–35.3) were significantly lower in DHCA + DR group compared with MHCA + ACP group. Conclusions: The results of our study demonstrate that DHCA + DR has the same prevalence of operative mortality, NE and association of death+PND than MHCA + ACP. However, the data suggests that DHCA + DR when compared with MHCA + ACP provides better renal protection and reduced prevalence of composite endpoint.